2012
DOI: 10.1002/gps.3902
|View full text |Cite
|
Sign up to set email alerts
|

Trends in psychotropic drug prescribing in Norwegian nursing homes from 1997 to 2009: a comparison of six cohorts

Abstract: Prescribing of psychotropic drugs in nursing homes has increased considerably, especially regarding antidepressants. Explanations for this trend need to be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
51
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 43 publications
8
51
2
3
Order By: Relevance
“…27,35 This study's observation that 12.1% of people ≥65 years old were prescribed one or more B&Zs, that is, one in four of the care home population and one in nine of the non-care home residents, with care home residents approximately three times more likely to have a B&Z prescribed, is also comparable to the wider literature, 2,25,[27][28][29]37 but is lower than that found among a Canadian sample. 1 This study found anxiolytic prescribing for non-care home residents to be comparable with previous studies.…”
Section: Comparison With Existing Literaturesupporting
confidence: 64%
See 2 more Smart Citations
“…27,35 This study's observation that 12.1% of people ≥65 years old were prescribed one or more B&Zs, that is, one in four of the care home population and one in nine of the non-care home residents, with care home residents approximately three times more likely to have a B&Z prescribed, is also comparable to the wider literature, 2,25,[27][28][29]37 but is lower than that found among a Canadian sample. 1 This study found anxiolytic prescribing for non-care home residents to be comparable with previous studies.…”
Section: Comparison With Existing Literaturesupporting
confidence: 64%
“…However, more personalised data are available for health boards and approved researchers. As with other studies of this nature, the lack of information on drug indications linked to prescribing is a limiting factor, 1,2,[27][28][29]35 but details of prescription indications in patients' clinical notes are known to be incomplete or lacking. 24 This may improve with the introduction of the Scottish Primary Care Resource (SPIRE), a collaboration between the Scottish Government and NHS National Services Scotland to simplify and standardise the process for extracting data from GP practice systems for audit, disease surveillance, benchmarking, planning, and research.…”
Section: 3 Lormetazepam (S) or Zaleplon (S)mentioning
confidence: 99%
See 1 more Smart Citation
“…El aumento del número de prescripciones de psicofármacos en residencias de ancianos a lo largo de los últimos años en la mayoría de los países desarrollados [11][12][13] convierte a este tipo de pacientes en uno de los grupos más consumidores de estos fármacos. Este argumento, unido a la importancia de la revisión de la medicación en residencias de ancianos, ya realizada en otros países [14], integrando en estos equipos de trabajo a un farmacéutico con competencias clínicas para detectar posibles medicamentos potencialmente inadecuados (MPI) y medicamentos potencialmente omitidos (MPO), trabajando siempre en un contexto multidisciplinar junto a médicos, enfermeros y otros profesionales sanitarios, además de las frecuentes caídas que sufre la población anciana, fueron razones de peso que nos llevaron a realizar este estudio.…”
Section: Introductionunclassified
“…Indeed, there has been a clear trend toward increasing rates of psychotropic drug prescription in nursing homes over time (Ruths et al, 2012).…”
mentioning
confidence: 99%